1997
DOI: 10.1073/pnas.94.22.11813
|View full text |Cite
|
Sign up to set email alerts
|

The crystal structure of human interferon β at 2.2-Å resolution

Abstract: Type I interferons (IFNs) are helical cytokines that have diverse biological activities despite the fact that they appear to interact with the same receptor system. To achieve a better understanding of the structural basis for the different activities of ␣ and ␤ IFNs, we have determined the crystal structure of glycosylated human IFN-␤ at 2.2-Å resolution by molecular replacement. The molecule adopts a fold similar to that of the previously determined structures of murine IFN-␤ and human IFN-␣ 2b but displays … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
130
0

Year Published

1998
1998
2012
2012

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 196 publications
(137 citation statements)
references
References 44 publications
7
130
0
Order By: Relevance
“…These predictions have been confirmed on the recently solved, three-dimensional structure of the human IFN-␤1a (37). The likelihood that Tyr 125 is a buried residue, involved in intramolecular bonds, was confirmed on the three-dimensional structure of human IFN-␤1a (37).…”
Section: Design Of Ifn-␤ Mutants-supporting
confidence: 64%
“…These predictions have been confirmed on the recently solved, three-dimensional structure of the human IFN-␤1a (37). The likelihood that Tyr 125 is a buried residue, involved in intramolecular bonds, was confirmed on the three-dimensional structure of human IFN-␤1a (37).…”
Section: Design Of Ifn-␤ Mutants-supporting
confidence: 64%
“…Type I IFNs belong to the class of helical cytokines (6) and are built by five helices. The structure of several type I IFNs have been resolved, such as murine IFN␤ (7), human IFN␣2 (8,9), human IFN␤ (10), and ovine IFN (11). Mutational studies have revealed functionally important residues on IFNs (reviewed in Ref.…”
Section: Type I Interferons (Ifn)mentioning
confidence: 99%
“…Type I IFNs belong to the class of helical cytokines and are built of five helices. The structures of human IFN-␣2 (3) and IFN-␤ have been resolved (4). The receptor structures are unknown, but can be modeled by homology to human cytokine receptors with known structures such as tissue factor (5) and IFN-␥ receptor (6).…”
mentioning
confidence: 99%